My dua book (KUTAB KHANA New Delhi, 2005)
"My Dua Book" is a collection designed to help children and families learn and understand the significance of various supplications (duas) in Islam. It typically includes simple, accessible duas for daily activities, prayers for specific needs, and explanations of their meanings. The book encourages the practice of making dua, fostering a connection with Allah, and instilling the importance of gratitude, guidance, and seeking help through prayer. It aims to inspire a habit of regular supplication and strengthen faith among young believers.